A Framework for Investigating Green Purchase Behavior with a Focus on Individually Perceived and Contextual Factors. Issue 1 (January 2023) - Asl, Roghayeh Teimourfamian; Khoddami, Soheila
The role of individually perceived and contextual factors on green purchase behavior (GPB) with a focus on the dimensions of consumer perceived value has been evaluated in this research. The basis of the model is a stimuli–organism–response (SOR) 1 framework, and the theory of planned behavior and the theory of consumption values have been combined. The research has been conducted on Iranian green consumers with green purchase experiences. It is an empirical study using the questionnaire survey method. Structural equation modelling (SEM) is utilized to measure the research framework. It has been revealed that individually perceived factors have more impact on GPB than contextual factors in this research. On the other hand, contextual factors do not affect the GPB of Iranian consumers. In addition, perceived social value had less effect on GPB than perceived emotional value. Therefore, the present study was likely proposed to fill the gap of previous studies, deprived of categorized factors affecting GPB focusing on internal and external approaches.